Effect of prepartum supplementation with calcium chloride on glucose and urea concentration and postpartum anestrus interval in Carora cows (Gaceta de Ciencias Veterinarias, 2020)
The objective of this study was to evaluate the effect of prepartum supplementation with calcium chloride on the serum concentration of energy metabolites (glucose and urea) during peripartum period and postpartum anestrus days. A completely randomized design was used using 24 multiparous Carora cows which were distributed in two groups of 12 animals each. A group was supplemented with 100g of calcium chloride/cow/day 21 days before the estimated calving day with a DCAD of -9.6 mEq / 100g DM. The second group was not supplemented. Glucose and urea concentrations as well as postpartum anestrus interval were determined on day 14 prepartum and 1, 15 and 45 days postpartum. The glucose concentration increased on days 15 and 30 postpartum in the supplemented group. The urea concentration increased on days 15 and 45 postpartum. There were no significant differences in the number of days from calving to first heat between groups. Based on the results it can be concluded that supplementation with 100g/cow/day of calcium chloride during prepartum in Carora cows, modifies the serum glucose and urea concentrations but has no effect on the reduction of the days from calving to the first heat.Key words: calcium chloride, Carora cows, glucose, urea, postpartum anestrus.